2012
DOI: 10.4187/respcare.01658
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Oximetry and Transcutaneous Carbon Dioxide in Home-Ventilated Neuromuscular Patients

Abstract: BACKGROUND: Pulse oximetry alone has been suggested to determine which patients on home mechanical ventilation (MV) require further investigation of nocturnal gas exchange. In patients with neuromuscular diseases, alveolar hypoventilation (AH) is rarely accompanied with ventilationperfusion ratio heterogeneity, and, therefore, oximetry may be less sensitive for detecting AH than in patients with lung disease. OBJECTIVE: To determine whether pulse oximetry (S pO 2 ) and transcutaneous carbon dioxide (P tcCO 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 19 publications
1
25
0
5
Order By: Relevance
“…While NPO has demonstrated some efficacy in the detection of nocturnal hypoventilation in specific disease populations such as ALS [57], it is possible to fail to identify patients with hypoventilation due to the absence of direct measurement of hypercarbia. Thus, while commonly used, NPO alone has shown to be a limited tool for diagnosis and monitoring of hypoventilation [58].…”
Section: Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…While NPO has demonstrated some efficacy in the detection of nocturnal hypoventilation in specific disease populations such as ALS [57], it is possible to fail to identify patients with hypoventilation due to the absence of direct measurement of hypercarbia. Thus, while commonly used, NPO alone has shown to be a limited tool for diagnosis and monitoring of hypoventilation [58].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…While not a direct measurement of PaCO 2 , transcutaneous and end-tidal sensors have been validated in clinic-based settings [59,60]. Recent technological advancements have increased the availability and quality of transcutaneous monitoring, and retrospective studies of homebased monitoring have demonstrated utility as a screening tool in conjunction with NPO [58,59].…”
Section: Laboratory Analysismentioning
confidence: 99%
“…L'hypoventilation alvéolaire donne une courbe de saturation plus basse avec des pics de désaturations cycliques correspondant à l'aggravation de l'hypoventilation liée au sommeil paradoxal. Une courbe de saturation normale n'élimine pas formellement une pathologie respiratoire du sommeil [8] (Fig. 1).…”
Section: La Démarche Du Diagnostic Et Du Traitementunclassified
“…Un essai de 30 minutes à une heure permettra de détecter les premiers inconvénients. Le réglage de la pression positive expiratoire (PEP) peut se faire de deux façons : manuellement, en partant d'une pression relativement faible (5 à 6 cm d'eau) avec correction en fonction de la polygraphie respiratoire ou à l'aide d'une PPC autotitrante [8], l'algorithme de la machine adapte la pression en fonction des événements respiratoires détectés. Il faut cependant noter qu'aucune PPC, à ce jour, n'est adaptée à la pédiatrie (< 30 kg).…”
Section: La Mise En Place Du Traitementunclassified
“…A transcutaneous technique using a Stow-Severinghaus electrochemical sensor 1 provides an alternative to arterial blood gas sampling and avoids the potential complications of aneurysms and limb ischemia. 2 Transcutaneous P CO 2 (P tcCO 2 ) monitoring is an accepted test in the homes of chronic users of nocturnal NIV, 3,4 but is still rarely used in the acute hospital setting. Studies have reported P tcCO 2 monitoring to be reliable over short time periods during acute NIV [5][6][7][8][9][10][11] and over 8 h during chronic NIV.…”
Section: Introductionmentioning
confidence: 99%